Penerapan Metode Experiential Learning untuk Meningkatkan Kemampuan Berpikir Kreatif pada Pembelajaran PAI dan Budi Pekerti - Rohim, Saepul; Fatimah, Yesa (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
Sharpening creative thinking skills in Islamic Religious Education is very necessary for the development of students. These creative thinking skills are needed to solve various kinds of problems. However, according to the Global Creativity Index (GCI) in 2017, it was stated that out of 127 countries researched, Indonesia was ranked 87th for the global creativity index with a score of 30.10. Likewise, the results of observations showed that the creative thinking skills of students in phase F of class XI-4 Animation of SMKN 4 Garut were still low, where only 38.10% of students were able to think creatively. To overcome this problem, the action taken was to apply the Experiential Learning method in Islamic Religious Education and Character Building learning. The purpose of this study was to describe the improvement of students' creative thinking skills using the Experiential Learning method. This study used the PTK research method, data collection techniques by conducting creative thinking ability tests on 21 students, interviews with teachers, observation and documentation. The data analysis technique was carried out through 3 stages, namely data reduction, data presentation and conclusion drawing. The results of the study showed that creative thinking skills can be improved after implementing the Experiential Learning method in phase F of class XI-4 Animation SMKN 4 Garut. The average creative thinking ability of students is in the good category because it can increase from 60% to 80%. Likewise, student learning outcomes from previously at an average of 45 increased to 80. Thus, all students have been able to meet the indicators of creative thinking skills comprehensively. Keywords: Creative Thinking Ability, Experiential Learning Method